(untitled) (American Journal of Islam and Society, 2003)
From the opening pages of the preface until the last sentence of the conclusion, this book is well-written, authoritative, and insightful. The author draws upon some 40 years of rich experience as an anthropologist in the Middle East and further afield to offer a clear analytical account of fundamentalism in the three monotheistic traditions of Christianity, Judaism, and Islam. His book also draws upon a decade of teaching and debate about fundamentalism with undergraduate students at the State University of New York at Binghamton, and the clarity of his writing reflects an appreciation of the needs and interests of students. Antoun defines the phenomenon of fundamentalism as “an orientation to the world, a particular worldview and ethos, and as a movement of protest and outrage against the rapid change that has overtaken the people of an increasingly global civilization at the end of the twentieth century.” He argues that it has defining characteristics wherever it is found: scripturalism (belief in the literal inerrancy of sacred scripture); the search for purity in an impure world; traditioning (making the ancient immediately relevant to the contemporary situation); totalism (taking religion beyond the worship center to home, school, workplace, bank, and elsewhere); activism (challenging establishments, both political and religious, sometimes by violent protest); struggle of good and evil; and selective modernization and controlled acculturation. These themes are explored in depth over the course of five chapters, with a sixth chapter based on a case study that presents a recording of conversations between the author and a “fundamentalist” in Jordan in 1986 ...